Effects of factors on response variables lap time and lower extremity range of motion in bobsleigh start using bobsleigh shoes for the 2018 Pyeongchang Winter Olympics - Park, S.; Lee, K.; Kim, D.; Yoo, J.; Jung, J.; Park, K. (Korean Journal of Sport Biomechanics, 2017)
Objective: The aim of this study was to analyze the effects of bobsleigh shoes on the lower extremity range of motion and start speed lap time and to develop bobsleigh shoes suitable for winter environments and Korean players based on sports science and optimized biomechanical performance. Background: The bobsleigh shoes used in the start section of the sport are one of the most important equipment for improving athletes' performances. Despite the importance of the start section, there are no shoes that are specifically designed for Korean bobsleigh athletes. Thus, Korean athletes have to wear sprint spike shoes instead of bobsleigh shoes to practice the start. Method: The subjects included four bobsleigh athletes from the Gangwon Province Bobsleigh Skeleton Federation. The study selected the bobsleigh shoe type A (company A) and type B (company B). We analyzed the lower extremity range of motion and sprint time (start line to 10 m) using a Motion Analysis System (USA). Results: In the measurement of the time required for the bobsleigh start section (10 m), the type A shoes demonstrated the fastest section record by 2.765±0.086 sec and yielded more efficient movements, hip and knee flexion, hip extension, ankle dorsiflexion, plantar flexion, and inversion than the type B shoes. Conclusion: Type A shoes can yield a better performance via effective lower extremity movements in the bobsleigh start section. Application: In the future, functional analysis should be conducted by comparing the upper material properties, comfort, and muscle fatigue of bobsleigh shoes based on the Type A shoes to develop such shoes suitable for Koreans.